MANAGEMENT SYSTEM IN TIME OF RESTRICTIONS - Kasim S. Biktyakov (Plekhanov Russian University of Economics, 2017)
Raising the production efficiency is an acute task of every Russian enterprise. To increase labour productivity we should first of all eliminate system restrictions - bottlenecks which hinder the production process. The author investigates issues of production optimization, which do not require additional investment and can find out growth reserves. In conditions of the crisis when enterprises cut their development budgets recommendations offered by the article can prevent false decisions. Management system in time of restrictions put forward by the author can help overcome the crisis and reach success.